2010
DOI: 10.1016/j.jclepro.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Energy management practices in Swedish energy-intensive industries

Abstract: Previous studies point out a large (untapped) potential for energy efficiency in industry through the adoption of energy management practices. The aim of this paper is to describe and analyze energy management practices in two different Swedish energyintensive industries: the pulp and paper industry and the foundry industry. The results show that one third of the studied mills and about two fifths of the studied foundries do not allocate energy costs by means of sub-metering, which probably contributes to rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
208
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(228 citation statements)
references
References 30 publications
13
208
1
6
Order By: Relevance
“…Though energy management practices has been scarcely studied (Caffal, 1995;Christofferson et al, 2006;Thollander and Ottosson, 2010), its importance has been demonstrated in several empirical studies of the manufacturing sector (Caffal, 1995;Christofferson, 2006;Thollander and Ottosson, 2010). Studies of the driving forces for energy efficiency in manufacturing industry demonstrate that long-term energy strategies and committed and skilled energy managers are important factors spurring energy efficiency in industrial firms.…”
Section: Energy Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Though energy management practices has been scarcely studied (Caffal, 1995;Christofferson et al, 2006;Thollander and Ottosson, 2010), its importance has been demonstrated in several empirical studies of the manufacturing sector (Caffal, 1995;Christofferson, 2006;Thollander and Ottosson, 2010). Studies of the driving forces for energy efficiency in manufacturing industry demonstrate that long-term energy strategies and committed and skilled energy managers are important factors spurring energy efficiency in industrial firms.…”
Section: Energy Managementmentioning
confidence: 99%
“…In fact, these studies indicate that such factors are ranked on parity with the driver cost reductions resulting from lower energy use (Thollander and Ottosson, 2008;Thollander et al, 2009). The adoption levels of energy management are low, even in energy-intensive industry; for example, a study of energy management practices in Swedish energyintensive industries revealed that only 25-40% of the companies could be described as successful when it came to energy management (Thollander and Ottosson, 2010).…”
Section: Energy Managementmentioning
confidence: 99%
“…Communication helps convincing the people (i.e., floor workers) about the importance of committing to the set goal and to managing feedback. People are more likely to act on information if it is specific and communicated in a personal manner by a person related to the receiver Ottosson 2008, Thollander andOttosson 2010). …”
Section: Theorymentioning
confidence: 99%
“…The leadership can show their commitment to energy efficiency through a project setup in which a full-time project leader is appointed to fully dedicate his/her time and knowledge to the project (Johansson 2015). The appointment of such a leader contributes to make the decision chain as short and efficient as possible, which is important for success of a project (Thollander and Ottosson 2010). However, the influence of the project leader depends very much on the leader's personal characteristics, e.g., ability to motivate others through interpersonal networking (Thollander and Ottosson 2008).…”
Section: Theorymentioning
confidence: 99%
“…O estudo também revela que o fator preponderante para a prática de gestão de energia é a redução de custo com enfoque em instalações elétricas e as informações que mais ajudam na decisão estão relacionadas à economia de energia do processo produtivo. Outro estudo feito em indústrias suecas também mostra que as práticas de gestão de energia dependem do tamanho da empresa e do uso intensivo de energia (Thollander & Ottosson, 2010).…”
Section: Barreiras De Gestãounclassified